Fitness Effects of Single Amino Acid Insertions and Deletions in TEM-1 β-Lactamase. Issue 12 (31st May 2019) - Gonzalez, Courtney E.; Roberts, Paul; Ostermeier, Marc
Abstract: Short insertions and deletions (InDels) are a common type of mutation found in nature and a useful source of variation in protein engineering. InDel events have important consequences in protein evolution, often opening new pathways for adaptation. However, much less is known about the effects of InDels compared to point mutations and amino acid substitutions. In particular, deep mutagenesis studies on the distribution of fitness effects of mutations have focused almost exclusively on amino acid substitutions. Here, we present a near-comprehensive analysis of the fitness effects of single amino acid InDels in TEM-1 β-lactamase. While we found InDels to be largely deleterious, partially overlapping deletion-tolerant and insertion-tolerant regions were observed throughout the protein, especially in unstructured regions and at the end of helices. The signal sequence of TEM-1 tolerated InDels more than the mature protein. Most regions of the protein tolerated insertions more than deletions, but a few regions tolerated deletions more than insertions. We examined the relationship between InDel tolerance and a variety of measures to help understand its origin. These measures included evolutionary variation in β-lactamases, secondary structure identity, tolerance to amino acid substitutions, solvent accessibility, and side-chain weighted contact number. We found secondary structure, weighted contact number, and evolutionary variation in class A beta-lactamases to be the somewhat predictive of InDel fitness effects. Graphical Abstract: Unlabelled Image Highlights: Fitness effects of insertions and deletions (InDels) are understudied. Quantified fitness effect of 4737 single amino acid InDels in TEM-1 β-lactamase Insertions are tolerated more than deletions except in a few regions. Relation between sequence/structural properties and fitness presented Weighted contact number and evolutionary variation somewhat predictive of tolerance